Pelancongan Budaya Melalui Festival : Dayang Nur Fatima Binti Abg Mohamad Festival Muzik Hutan Hujan Sedunia Di Kuching Sarawak - Dayang Nur Fatima, Binti Abg Mohamad. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This research is about the effectiveness of festival as medium to promote Sarawak culture in Rainforest World Music Festival in Kuching Sarawak. This festival are involve various participant from a different country to join in together promoting their culture. In data collection, this research required an involvement of international visitors, participant and organizer of the event. The qualitative method was use in analyzing the data obtain. The research finding could be utilized by the organizer to improve the strategy in promoting Sarawak culture in the future.